A simple model for material's strengthening under high pressure torsion. (5th June 2016) - Khoddam, S.; Hodgson, P.D.; Zarei-Hanzaki, A.; Yan Foon, Leong
Abstract: Constrained high pressure torsion (CHTP) is a promising route to fabricate ultra-fine structured bulk and powder materials. It was recently proposed as a mechanical test for large strains. Only a few models are available on "friction induced deformation" during CHTP. A number of closed form models were derived in this work to estimate a sticking friction condition during CHPT. The models also correlate CHPT's torque-twist-pressure response and its constitutive parameters. To verify the accuracy of the derivations, the response for Armco iron samples were estimated under three different pressures of 1.9, 3.8 and 7.5 GP and compared with experimental data. Contribution of frictional power dissipated at the specimen's circumferential surface was evaluated and compared with the total deformation power. Graphical abstract: Highlights: Solved confined high pressure torsion process' governing equations Enabled estimation of friction induced deformation by the process Estimated friction's contribution into the total consumed power Verified the solution using experimental case studies